2021
DOI: 10.1007/s12559-021-09839-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Expansion of Domain-Specific Affective Models for Web Intelligence Applications

Abstract: Sentic computing relies on well-defined affective models of different complexity—polarity to distinguish positive and negative sentiment, for example, or more nuanced models to capture expressions of human emotions. When used to measure communication success, even the most granular affective model combined with sophisticated machine learning approaches may not fully capture an organisation’s strategic positioning goals. Such goals often deviate from the assumptions of standardised affective models. While certa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The survey identifies six large communities (social media, ML, NLP, opinion mining, Arabic, semi-supervised learning) and their key research topics. Domain-specific affective models [20] go beyond classic models by incorporating application-specific affective categories and interpreting them based on the situational context. An affective model for benchmarking TV shows, for example, might consider fear and sadness to be desirable associations rather than undesirable ones.…”
Section: Affective Modelsmentioning
confidence: 99%
“…The survey identifies six large communities (social media, ML, NLP, opinion mining, Arabic, semi-supervised learning) and their key research topics. Domain-specific affective models [20] go beyond classic models by incorporating application-specific affective categories and interpreting them based on the situational context. An affective model for benchmarking TV shows, for example, might consider fear and sadness to be desirable associations rather than undesirable ones.…”
Section: Affective Modelsmentioning
confidence: 99%
“…The selection of the knowledge extraction techniques was guided by the research framework discussed in Section 4, which requires (i) the analysis and tracking of major stakeholders, (ii) the identification of dominant issues, and (iii) the classification of media criticism as either optimistic-constructive or negative. Weichselbraun et al [37] discussed the use of domain-specific affective models, which support capturing emotions that go beyond standard sentiment and emotion models. An assessment that compared the optimisticconstructive and negative dimensions from communication science literature with standard sentiment polarity (dimensions: positive and negative) concluded that, for the purpose of the joint research project, the use of sentiment polarity is an efficient (availability of high-quality sentiment lexicons) and effective (sufficiently high correlation between both metrics) strategy.…”
Section: Knowledge Extractionmentioning
confidence: 99%
“…The significance of marketing communication has surged, reflecting the market's increasing complexity and consumers' evolving expectations. This field is central to establishing, nurturing, and fortifying the relationship between companies and their customers through a blend of diverse tools, strategies, and tactics, allowing companies to highlight their strengths, narrate their stories, and position their offerings in a competitive marketplace (Weichselbraun, Steixner, Braşoveanu, Scharl, Göbel & Nixon, 2022). Historically, marketing communication strategies like traditional advertising, including billboards, print ads, and radio spots, were predominant.…”
Section: Introductionmentioning
confidence: 99%